2003
DOI: 10.5897/ajb2003.000-1093
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ivermectin and thiabendazole in the treatment of uncomplicated human Strongyloides stercoralis infection

Abstract: Ivermectin is the drug of choice in the treatment of onchocerciasis, and has been proven to be highly effective against Strongyloides stercoralis. This study compares ivermectin's efficacy and safety with that of thiabendazole, an established drug of choice for strongyloidiasis, in 252 confirmed cases of uncomplicated human intestinal strongyloidiasis. Subjects were administered orally with ivermectin (200 µg/kg) in a single dose or thiabendazole, 25 mg/kg, twice daily (50mg/kg/day) for 3 consecutive days. Sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“… 6 Ivermectin monotherapy has high efficacy against S. stercoralis and A. lumbricoides , moderate efficacy against T. trichiura , and poor efficacy against hookworms. 6 , 10 , 11 , 12 Our findings generally align with previous efficacy trials and cross-sectional studies comparing onchocerciasis-treated to untreated areas, that demonstrated substantial reductions in S. stercoralis prevalence and moderate reductions in T. trichiura prevalence and intensity, associated with one dose of ivermectin MDA. 10 , 11 , 12 , 16 , 17 , 18 The marginal non-significant prevalence reduction for Stronygloides spp.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“… 6 Ivermectin monotherapy has high efficacy against S. stercoralis and A. lumbricoides , moderate efficacy against T. trichiura , and poor efficacy against hookworms. 6 , 10 , 11 , 12 Our findings generally align with previous efficacy trials and cross-sectional studies comparing onchocerciasis-treated to untreated areas, that demonstrated substantial reductions in S. stercoralis prevalence and moderate reductions in T. trichiura prevalence and intensity, associated with one dose of ivermectin MDA. 10 , 11 , 12 , 16 , 17 , 18 The marginal non-significant prevalence reduction for Stronygloides spp.…”
Section: Discussionsupporting
confidence: 86%
“…Ivermectin is a broad-spectrum antiparasitic drug that has high therapeutic efficacy against S. stercoralis and A. lumbricoides , moderate efficacy against T. trichiura , and poor efficacy against hookworms. 6 , 10 , 11 , 12 The combination of albendazole and ivermectin has excellent efficacy against all species. 6 …”
Section: Introductionmentioning
confidence: 99%